PENERAPAN ASSOCIATION RULE MINING PADA REKOMENDASI BUNDLING PRODUK MINIMARKET MENGGUNAKAN ORACLE DATA MINER - Husni Iskandar Pohan; Boby Siswanto (J-Icon : Jurnal Komputer dan Informatika, 2021)
Buying and selling is a process that involves sellers and buyers or consumers where transactions occur that result in the exchange of goods for money. The seller will try to sell the goods by getting the maximum profit possible, while the buyer will get the goods at the minimum possible cost. One of the places where buying and selling transactions are potential is a minimarket. Minimarkets provide a variety of goods that buyers need, but there are times when there are goods that are not in demand by buyers, causing losses to the minimarket. There is an association rule mining technique that can find links between one item and another. The purpose of this study is to provide product bundling recommendations in the form of combining two products with one price to optimize minimarket sales. The results of this study are a list of product recommendations that are included in product bundling.